A Highly Sensitive and Stable rGO:MoS2-Based Chemiresistive Humidity Sensor Directly Insertable to Transformer Insulating Oil Analyzed by Customized Electronic Sensor Interface - Adib, Md Ridwan; Lee, Yongbum; Kondalkar, Vijay V.; Kim, Sihyeok; Lee, Keekeun (ACS Sensors, 2021)
Reduced graphene oxide and molybdenum disulfide (rGO:MoS2) are the most representative two-dimensional materials, which are promising for a humidity sensor owing to its high surface area, a large number of active sites, and excellent mechanical flexibility. Herein, we introduced a highly sensitive and stable rGO:MoS2-based humidity sensor integrated with a low-power in-plane microheater and a temperature sensor, directly insertable to transformer insulating oil, and analyzed by a newly developed customized sensor interface electronics to monitor the sensor's output variations in terms of relative humidity (RH) concentration. rGO:MoS2 sensing materials were synthesized by simple ultrasonication without using any additives or additional heating and selectively deposited on titanium/platinum (Ti/Pt) interdigitated electrodes on a SiO2 substrate using the drop-casting method. The significant sensing capability of p-n heterojunction formation between rGO and MoS2 was observed both in the air and transformer insulating oil environment. In air testing, the sensor exhibited an immense sensitivity of 0.973 kω/%RH and excellent linearity of ∼0.98 with a change of humidity from 30 to 73 %RH, and a constant resistance deviation with an inaccuracy rate of 0.13% over 400 h of continual measurements. In oil, the sensor showed a high sensitivity of 1.596 kω/%RH and stable repeatability for an RH concentration range between 34 and 63 %RH. The obtained results via the sensor interface were very similar to those measured with a digital multimeter, denoting that our developed total sensor system is a very promising candidate for real-time monitoring of the operational status of power transformers.
Keywords: Concentration ranges; Electronic sensor interface; Inter-digitated electrodes; Mechanical flexibility; Number of active sites; Real time monitoring; Sensor interface electronics; Two-dimensional materials; Electronics; Graphite; Humidity; Molybdenum; Silicon Dioxide; humidity sensor; in-plane microheater; molybdenum disulfide; reduced graphene oxide; temperature sensor; transformer insulating oil